Effects of the opioid receptor antagonist naltrexone on smoking and related behaviors in smokers preparing to quit: a randomized controlled trial. (12th July 2013) - King, Andrea; Cao, Dingcai; Zhang, Lingjiao; Rueger, Sandra Yu
Abstract: Aims: To determine if naltrexone affects smoking behaviors in smokers preparing to quit, and whether or not such pre‐quit responses predict post‐quit date outcomes. Design: Double‐blind, placebo‐controlled, randomized study. The current study focused on smoking‐related outcomes in the pre‐quit phase, which was 1 week prior to the quit date, and these findings were linked with reductions in the same outcomes demonstrated in the post‐quit phase published previously for this randomized controlled trial (RCT) in mediation analyses. Setting: Community sample of adult smokers desiring to quit in Chicago, Illinois, USA. Participants: Participants were 315 smokers randomized to naltrexone ( n  = 161; mean age = 42.58 years; 60% Caucasian) or placebo ( n  = 154; mean age = 41.32 years; 55% Caucasian). Measurements: The difference from baseline in the number of cigarettes smoked during the pre‐quit phase interval was the primary outcome. Secondary pre‐quit outcomes were assessed using Likert scales of subjective responses and consumption of cigarettes, alcohol and food. Number of cigarettes smoked, alcoholic drinks consumed and the Brief Questionnaire of Smoking Urges were assessed in the post‐quit phase. Findings: Relative to placebo, naltrexone decreased the number of cigarettes smoked (−4.21 versus −2.93, P  < 0.05), smoking urge ( P  = 0.02) and number of alcoholic drinks consumed ( P  = 0.04). Exploratory mediation analyses linking outcomes of the pre‐quit and post‐quit phases found that naltrexone's effects on reducing smoking urge, cigarettes smoked and alcoholic drinks consumed in the pre‐quit phase demonstrated full mediation of their respective effects during the post‐quit phase. Conclusions: Naltrexone taken in the week before a quit attempt reduces cigarette consumption, urges to smoke and alcohol consumption relative to placebo. The size of the effect mediates statistically the size of similar effects after the quit date.